Short Hypoxia Does not Affect Plasma Leptin in Healthy Men under Euglycemic Clamp Conditions. (22nd April 2009) - Schmoller, Andre; Voss, Michaela; Gehring, Hartmut; Rudolf, Sebastian; Schweiger, Ulrich; Schultes, Bernd; Oltmanns, Kerstin M.
Abstract : Leptin is involved in the endocrine control of energy expenditure and body weight regulation. Previous studies emphasize a relationship between hypoxic states and leptin concentrations. The aim of this study was to investigate the effects of acute hypoxia on leptin concentrations in healthy subjects. We examined 14 healthy men. Hypoxic conditions were induced by decreasing oxygen saturation to 75% for 30 minutes. Plasma leptin concentrations were determined at baseline, after 3 hours of euglycemic clamping, during hypoxia, and repeatedly the following 2.5 hours thereafter. Our results show an increase of plasma leptin concentrations in the course of 6 hours of hyperinsulinemic-euglycemic clamping which may reflect diurnal rhythmicity. Notwithstanding, there was no difference between levels of leptin in the hypoxic and the normoxic condition (P = .2 ). Since we did not find any significant changes in leptin responses upon hypoxia, plasma leptin levels do not seem to be affected by short hypoxic episodes of moderate degree.